The Validity of the Electronic Signature in Electronic General Meeting of Shareholders S of the Limited Company’s - Ikhsan Lubis (Universitas Syiah Kuala, 2021)
The enactment of electronic signatures, especially at the General Meeting of Share-holders (GMS) and responses to legal actions from electronic signatures in the deed of Decision of the General Meeting of Shareholders in a Limited Liability Company, will be confronted by the progress of the era and the legality of the deed. This research method is classified as normative research, the approach method is descriptive analytical. This study shows that the regulation of electronic signatures on the deed of the Statement of Shareholders' Meeting Resolutions is the development of the form of legal evidence. For this reason, the form of evidence is made in the form of electronic information or electronic documents. The effect of the signing if it is done through electronic media, namely the result of the GMS decision has a legal impact on the status of ratification in the law. If the GMS has an electronic signature so that the legality of the legal action is recognized, the government and especially the legislators make legal rules to regulate with certainty the validity of the results of the GMS electronically, so that legal certainty is formed.